(untitled) (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
European powers partitioned the African continent in an abstract manner, disregarding ancient tribal boundaries, history, or the traditions of the conquered peoples, and without any intention of creating a constellation of nation-states modeled after their own. The countries they invented became nations following decolonization, and these nation-states required ideological underpinning because, beneath the superficial structures overlaying the whole, a tribal reality persisted. A crisis of nationalism and its paradigms emerged early on—a crisis that appeared intertwined with issues of tribalism and ethnicity. African intellectuals sought to respond to this by forging a collective identity. The schools of thought in Dakar, Ibadan, and Dar es Salaam hoped—by advocating for a unified African civilization—to represent an African reality that had lost its coherence amidst a logic of division. This new identity was to be built upon a conceptual geographical redefinition of Africa and a reinterpretation of the continent's history. The emergence of the first human being in this region and the birth—also within this territory—of the brilliant, Black African-originated Egyptian civilization stand as two of the founding myths of this new collective identity.